The Influence of Logistics 4.0 Tools on Sustainable Development: Delphi Study - Michał ADAMCZAK; Jędrzej JANKOWSKI-GUZY (Communications of International Proceedings, 2021)
Background: The development of technologies and tools used in logistics 4.0 requires checking their impact on the sustainable development of enterprises and economies. Only experts with knowledge and experience in both fields can answer this question. Methods: The delphi method was used. In the analysis of the results, data visualization, the dispersion index and the verification of statistical hypotheses with the Friedman test were used. Results: The aim of the study is to present an analysis of experts' opinions on the impact of logistics 4.0 tools on economic development and its sustainability. In the case of logistics 4.0 tools, it is possible to divide them into two groups: those that have a positive impact on the implementation of the sustainable development concept (e.g. shipment tracking, truck tracking, electronic data interchange, and those that have a negative impact (e.g. augmented reality, cobots , autonomous robot). Conclusions: When analyzing the support for Logistics 4.0 tools of individual SD components, it should be noted that, according to experts, the economic aspect is supported the most. Modern tools used in logistics may pose a threat to development in the social aspect.
Keywords: Logistics 4.0; sustainable development; delphi study